Mechanistic dissection of macro- and micronucleophagy - Otto, Florian B. (Autophagy, 2020)
Nucleophagy, the mechanism for autophagic degradation of nuclear material, occurs in both a macro- and micronucleophagic manner. Upon nitrogen deprivation, we observed, in an in-depth fluorescence microscopy study, the formation of micronuclei: small parts of superfluous nuclear components surrounded by perinuclear ER. We identified two types of micronuclei associated with a corresponding autophagic mode. Our results showed that macronucleophagy degraded these smaller micronuclei. Engulfed in Atg8-positive phagophores and containing cargo receptor Atg39, macronucleophagic structures revealed finger-like extensions when observed in 3-dimensional reconstitutions of fluorescence microscopy images, suggesting directional growth. Interestingly, in the late stages of phagophore elongation, the adjacent vacuolar membrane showed a reduction of integral membrane protein Pho8. This change in membrane composition could indicate the formation of a specialized vacuolar domain, required for autophagosomal fusion. Significantly larger micronuclei formed at nucleus vacuole junctions and were identified as a substrate of piecemeal microautophagy of the nucleus (PMN), by the presence of the integral membrane protein Nvj1. Micronuclei sequestered by vacuolar invaginations also contained Atg39. A detailed investigation revealed that both Atg39 and Atg8 accumulated between the vacuolar tips. These findings suggest a role for Atg39 in micronucleophagy. Indeed, following the degradation of Nvj1, an exclusive substrate of PMN, in immunoblots, we could confirm the essential role of Atg39 for PMN. Our study thus details the involvement of Atg8 in both macronucleophagy and PMN and identifies Atg39 as the general cargo receptor for nucleophagic processes. Abbreviations: DIC: Differential interference contrast, FWHM: Full width at half maximum, IQR: Interquartile range, MIPA: Micropexophagy-specific membrane apparatus, NLS: Nuclear localization signal, NVJ: Nucleus vacuole junction, PMN: Piecemeal microautophagy of the nucleus, pnER: Perinuclear ER.